Analysis Of Policy Has Been Established By The Minister On Opening The Export Of Lobster Seed In Indonesia - Kyaw, Aung Ye; Jalil, Jalil (Maritime Park: Journal of Maritime Technology and Society, 2022)
Seakeeping is the ship's ability to stay afloat on the waves. The ship's maneuverability is greatly influenced by external factors related to the state of the sea and the waters in which the ship sails. Calculating seakeeping with various variations of depth, current, and wave height is needed for ship safety when sailing in the calculation of seakeeping using linear strip theory to calculate the response of heaving and pitching movements while roll damping theory for rolling movements. In this study, the ship's motion is calculated using the Finite element method software Hydrodynamic Diffraction and Hydrodynamic Time Response. For variations in wave height and water depth, referring to the conditions of Indonesian waters, from the reference, variations in wave height of 3 m, and 5 m (based on sea state WMO). In contrast, the current variation uses a current with a speed of 10 knots and a current depth of 10 T, 15 T, and 20 T. Based on the data obtained in data processing, it can be seen that the high value of the wave frequency obtained at 90 and 270 degrees wave direction is relatively high. The value of the roll spectrum in the direction of 0 and 270 degrees is large and can cause rolling on the ship. In the direction of 0 and 270 degrees, the wave resistance can be reduced by th Lobsters are animals that enter into crustaceans that have problematic skin. Adult lobsters can generally be found on a stretch of sand with coral spots with a depth of between 5-100 meters. This condition will cause a low number of young lobsters in the waters. This research was conducted with a case study regarding the policy of opening lobster seed export, which aims to find out how the policy is to open the export of lobster seed. The data obtained is done by reviewing the literature on the internet. Based on the analysis, the export profit of lobster seeds has continued to increase every month since it was again allowed by the government in May 2020. Based on data from the Central Statistics Agency (BPS), lobster seeds began to be re-exported in June 2020 at 32 kilograms, costing the US $ 112,990. The government can help with training and outreach on lobster cultivation. The government can offer Lobster a partnership package to help people start a freshwater crayfish business.